THE CHARACTERISTICS OF THE BOARD OF COMMISSIONERS, COMPANY CHARACTERISTICS AND FINANCIAL DISTRESS AT FERTILIZER COMPANIES IN INDONESIA - Priyanto Priyanto; Rahmat Setiawan (SEAN Institute, 2023)
The purpose of this study is to analyze the impact of the corporate governance which are represented by the board of commissioners' characteristics and company characteristics which are the main parameters of its financial ratios on the possibility of financially distressed at fertilizer companies in Indonesia. This observe involves five fertilizer companies which has dominant market in Indonesia by using secondary data's taken from the business enterprise's financial statements in 2012 to 2021. The logistic regression showed that the adoption of corporate governance especially the qualification of commissioners can improve company's performance and allow to avoid the possibility of financial distress. This study also indicates that liquidity and profitability have a strong negative impact on the possibility of financial distress. On the other hand, solvency has a strong positive impact on the possibility of corporate financial distress.